Kidney Function in Patients With Neuromuscular Disease: Creatinine Versus Cystatin C - Screever, Elles M.; Kootstra-Ros, Jenny E.; Doorn, Joyce; Nieuwenhuis, Jellie A.; Meulenbelt, Henk E. J.; Meijers, Wouter C.; de Boer, Rudolf A. (Frontiers in Neurology, 2021)
Background: Accurate measurement of kidney function in patients with neuromuscular disorders is challenging. Cystatin C, a marker not influenced by skeletal muscle degradation, might be of clinical value in these patients. Methods: We consecutively enrolled 39 patients with neuromuscular disorders. We investigated the correlation of the eGFR, based on plasma creatinine and Cystatin C, with clinical and biochemical variables associated with kidney function, namely age and galectin-3. Results: Creatinine-based eGFR was 242 (± 80) and Cystatin C-based eGFR was 110 (± 23) mL/min/1.73 m2. Cystatin C-based eGFR was correlated with age (β -0.63 p<0.0001) and galectin-3 levels (β -0.43 p<0.01), while creatinine-based eGFR was not (β -0.22 p=0.20; β -0.28 p=0.10). Sensitivity analyses in Duchenne and Becker patients revealed the same results: Cystatin C-based eGFR was correlated with age (β -0.61 p<0.01) and galectin-3 levels (β -0.43 p=0.05), while creatinine-based eGFR was not (β -0.32 p=0.13; β -0.34 p=0.14). Conclusions: These data indicate that estimation of renal function in patients with neuromuscular disorders cannot reliably be achieved with creatinine, while Cystatin C appears a reasonable alternative. Since a large proportion of patients with neuromuscular disorders develops heart failure, and requires heart failure medication, adequate monitoring of renal function is warranted.